Antioxidant capacities, antidiabetic potentials, and mineral compositions of pap aqua and aqueous extracts from Ocimum gratissimum L. - Oludare Shadrach Agunbiade; Olakunle Bamikole Afolabi; Kikelomo Folake Jaiyesimi; Olusola Bolaji Adewale; Patrick Osemeyekeh Okoh; Ezekiel Adewole; Samson Olatunde Mabayoje; Esther Kemi Agboola (Shahrekord University of Medical Sciences, 2024)
Introduction: This study appraised the antioxidant potentials, mineral compositions, and antidiabetic activities of pap water (aqua) extract (PWE) and aqueous extract (AE) from Ocimum gratissimum. Methods: The total phenolic contents (TPC), total flavonoid contents (TFC), ferric reducing antioxidant powers (FRAP), Fe2+-chelating abilities, 1,1-diphenyl-2-picrylhydrazyl (DPPH) free radical scavenging abilities, and enzymes inhibition potentials of the PWE and AE from O. gratissimum were evaluated. Additionally, mineral contents were determined using absorptive absorbance spectroscopy (AAS). Results: The PWE of O. gratissimum exhibited higher TPC of 42.61± 0.04 mg gallic acid equivalent per gram of dried sample (GAE/g) and TFC of 85.7 ± 0.02 µg quercetin equivalent per gram of dried sample (QE/g). In contrast, AE had lower TPC (21.52 ± 0.01 mg GAE/g) and TFC (55.0 ± 0.01 µg QE/g). PWE also displayed a lower FRAP of 2.86 ± 0.01 mg AAE/g, while AE had a higher FRAP of 2.94 ± 0.03 mg AAE/g. PWE of O. gratissimum had IC50 for DPPH: 100.00 µg/mL, Fe2+-chelating ability: 4.41 µg/mL, while AE had IC50 for DPPH: 140.00 µg/mL and Fe2+-chelating ability: 4.90 µg/mL. Similarly, the PWE of O. gratissimum showed a higher α-amylase inhibition (IC50: 0.47 mg/mL) than AE (IC50: 0.78 mg/mL); however, AE (IC50 =3.09 µg/mL) demonstrated a higher α-glucosidase inhibition than PWE (IC50: 9.09 µg/mL). AAS analyses indicated the presence of Ca, Fe, Mg, Cu, Zn, and Mn in different proportions in both extracts. Conclusion: Therefore, PWE could be a better alternative in the management of diabetes melitus if properly annexed.